2011
DOI: 10.1111/j.1813-6982.2011.01260.x
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Performance of an Estimated Dsge Model for the South African Economy

Abstract: We construct a small open‐economy New Keynesian dynamic stochastic general equilibrium (DSGE) model for South Africa with nominal rigidities, incomplete international risk sharing and partial exchange rate pass‐through. The parameters of the model are estimated using Bayesian methods, and its out‐of‐sample forecasting performance is compared with Bayesian vector autoregression (VAR), classical VAR and random‐walk models. Our results indicate that the DSGE model generates forecasts that are competitive with tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 72 publications
(116 reference statements)
2
15
0
Order By: Relevance
“…Gupta and Kabundi (2010), when using a small-open economy DSGE model to forecast the nominal effective exchange rate depreciation, shows the ability of such a model to outperform not only classical and Bayesian VARs based on a small set of predictors, but also large-scale factor models and Bayesian VARs relying on 266 macroeconomic time-series. Similar results were obtained by Alpanda et al, (2011) based on a relatively more sophisticated small-open economy DSGE model. The authors found that the DSGE model consistently outperformed the random-walk model in forecasting, the depreciation of the nominal rand-dollar exchange rate, and also performed better, in general, than the smallscale VAR and Bayesian VARs, based on a set ten fundamental variables.…”
Section: Introductionsupporting
confidence: 83%
“…Gupta and Kabundi (2010), when using a small-open economy DSGE model to forecast the nominal effective exchange rate depreciation, shows the ability of such a model to outperform not only classical and Bayesian VARs based on a small set of predictors, but also large-scale factor models and Bayesian VARs relying on 266 macroeconomic time-series. Similar results were obtained by Alpanda et al, (2011) based on a relatively more sophisticated small-open economy DSGE model. The authors found that the DSGE model consistently outperformed the random-walk model in forecasting, the depreciation of the nominal rand-dollar exchange rate, and also performed better, in general, than the smallscale VAR and Bayesian VARs, based on a set ten fundamental variables.…”
Section: Introductionsupporting
confidence: 83%
“…When considering these results we note that the smoothing coefficient, ρ, in the two models differ slightly. In the model that does not include any switching we have a coefficient of 0.82, which is similar to the value that was obtained in Alpanda et al (2011). In the Makov-switching model the posterior estimate for the interest rate smoothing coefficients are ρ(κ = 1) = 0.87 and ρ(κ = 2) = 0.90, which allows for greater smoothing in the interest rate.…”
Section: In-sample Statisticssupporting
confidence: 59%
“…Thereafter, we are able to initialize the Markov Chain Monte Carlo (MCMC) procedure that is used to construct the full posterior distribution and marginal data density. Details of the prior parameter values that are used in the calculation of the posterior estimates are similar to those that were used in Alpanda et al (2011) and are provided along with all the posterior estimates in Table 2.…”
Section: Solution and Estimationmentioning
confidence: 94%
See 1 more Smart Citation
“…Recent studies, namely, Liu and Gupta (2007), Liu et al (2009Liu et al ( , 2010, Gupta and Kabundi (2010, forthcoming) and Alpanda et al (2011), have initiated a growing interest in forecasting macroeconomic variables in South Africa using Dynamic Stochastic General Equilibrium (DSGE) models.…”
Section: Table Of Contents 1 Introductionmentioning
confidence: 99%